Comparison of nocturnal symptoms in advanced Parkinson’s disease patients with sleep disturbances: pramipexole sustained release versus immediate release formulations - Xiang W; Sun YQ; Teoh HC (Dove Medical Press, 2018)
Wei Xiang,1 Ya Qing Sun,2 Hui Chin Teoh3 1Medical Affairs, Boehringer Ingelheim (China) Investment Co. Ltd, Shanghai, People’s Republic of China; 2Biostatistics and Data Sciences, Boehringer Ingelheim (China) Investment Co. Ltd, Shanghai, People’s Republic of China; 3Clinical Operations, Boehringer Ingelheim (China) Investment Co. Ltd, Shanghai, People’s Republic of China Background: Nocturnal symptoms are common in Parkinson’s disease (PD), which greatly affect the quality of life but are often overlooked in clinical settings. Treatment strategies that provide sustained dopaminergic stimulation may have sleep benefits. Objective: To investigate the treatment effects of pramipexole (PPX) sustained release (SR) versus PPX immediate release (IR) on nocturnal symptoms in advanced PD patients with sleep disturbances. Materials and methods: In this study, the PPX clinical trial (NCT00466167) was retrospectively analyzed for PD Sleep Scale (PDSS) total and domain scores in patients with advanced idiopathic PD receiving either PPX SR or PPX IR, who experienced motor fluctuations while on stable levodopa with a baseline PDSS total score of <90, indicating sleep disturbances. Analysis of covariance test was used to compare the adjusted mean changes at week 18 from baseline between treatment groups, after adjusting for pooled country and baseline scores. Results: A total of 119 patients with PD reported sleep disturbances at baseline (PDSS <90; SR, n=59; IR, n=60). At week 18, patients receiving PPX SR reported numerically greater improvement of sleep disturbance than those receiving PPX IR, although the difference of 6.8 points was not statistically significant (adjusted mean changes in PDSS total score, SR=28.5 versus IR=21.7 points, P=0.165). Patients receiving PPX SR observed a numerically greater adjusted mean change in all PDSS domains compared with PPX IR. The overall proportions of patients with any adverse event were similar between both PPX SR and IR groups (62.7% versus 70.0%). Conclusion: Both the PPX formulations showed improvements in nocturnal symptoms in advanced PD patients with sleep disturbances and were generally well tolerated. Given the known pharmacokinetic profile of an SR formulation and numerical advantage in PDSS mean change over IR formulation, these preliminary evidences support future prospectively designed studies to investigate the effects of PPX SR for improved sleep. Keywords: dopamine agonist, efficacy, nonmotor symptoms, Parkinson’s disease, Parkinson’s Disease Sleep Scale, pramipexole extended release